Impacts of Engineered Diversions and Natural Avulsions on Delta‐Lobe Stability. Issue 13 (9th July 2021) - Carlson, Brandee N.; Nittrouer, Jeffrey A.; Swanson, Travis E.; Moodie, Andrew J.; Dong, Tian Y.; Ma, Hongbo; Kineke, Gail C.; Pan, Minglong; Wang, Yuanjiang
Abstract: Reduced sediment supply and rising sea levels are driving land submergence on deltas worldwide, motivating engineering practices that divert water and sediment to sustain coastal landforms. However, lobe response following channel abandonment by diversions has not been constrained by field‐scale studies. Herein, avulsion and engineered diversion scenarios are explored for the Huanghe delta (China), where three lobes were abandoned in the last 40 yr. Two lobes were completely cut off by diversions, and one naturally by an avulsion. Shoreline retreat rates are strikingly different: ∼400 m/yr for diverted lobes and ∼90 m/yr for avulsed lobe. We hypothesize that this variability is linked to vegetal cover across lobes, and therefore the capacity to buffer hydrodynamic reworking of shoreface sediment. Furthermore, the vegetal cover is related to lobe salinity and elevation, which vary by abandonment style. We offer this as a case study to inform about the efficacy of future delta diversions. Plain Language Summary: Sediment and water diversions are an important tool to combat land loss of deltaic coastlines. However, nourishment of drowned coastal land typically requires diverting water and sediment away from another region of the coast, potentially resulting in additional land loss. This study finds that the stability of shorelines facing reduced sediment supply is dependent on elevation before sediment loss, freshwater supply, and vegetation coverage. These findings have implications for future sediment and water diversions, by informing strategies that optimize land preservation. Key Points: Coastline retreat following channel abandonment is assessed for engineered diversions and natural avulsions on the Huanghe delta (China) Antecedent channel topography, riverine water input, and vegetation vary depending on abandonment style, and impact delta lobe stability By mimicking conditions for natural channel avulsions, lobes abandoned by engineering practices may be made resilient to shoreline retreat